2008
DOI: 10.1158/1541-7786.mcr-07-2105
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of the Human Glutathione S-Transferase P1 Gene as a Novel Transcriptional Target of the p53 Tumor Suppressor Gene

Abstract: The glutathione S-transferase P1 (GSTP1) is involved in multiple cellular functions, including phase II metabolism, stress response, signaling, and apoptosis. The mechanisms underlying the significantly high GSTP1 expression in many human tumors are, however, currently not well understood. We report here that the GSTP1 gene is a heretofore unrecognized downstream transcriptional target of the tumor suppressor p53. We identified a p53-binding motif comprising two consecutive half-sites located in intron 4 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 35 publications
(38 reference statements)
3
33
0
1
Order By: Relevance
“…In contrast to mice, GSTP expression is restricted to the biliary epithelium in normal human liver. A number of transcription binding sites, such as AP-1 (Moffat et al, 1997), p53 (Lo et al, 2008), retinoic acid, and nuclear factor kB (Xia et al, 1993), have been identified within the human GSTP gene. Recently, we have made further efforts to characterize the regulation of human GSTP1 in an animal model and demonstrated upregulation of human hepatic GSTP expression in response to the chemopreventive agents ethoxyquin and butylated hydroxyanisole (Henderson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to mice, GSTP expression is restricted to the biliary epithelium in normal human liver. A number of transcription binding sites, such as AP-1 (Moffat et al, 1997), p53 (Lo et al, 2008), retinoic acid, and nuclear factor kB (Xia et al, 1993), have been identified within the human GSTP gene. Recently, we have made further efforts to characterize the regulation of human GSTP1 in an animal model and demonstrated upregulation of human hepatic GSTP expression in response to the chemopreventive agents ethoxyquin and butylated hydroxyanisole (Henderson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This in vivo evidence is unique in showing that Gstp can alter tumorigenicity in a model that does not involve carcinogens, and suggests that variation in GSTP expression could influence colon cancer susceptibility. Human GSTP can be regulated by a number of pathways including AP1, retinoic acid, and p53 signaling (17)(18)(19). Using a mouse humanized for the Gstp gene, we are currently investigating whether GSTP can be regulated in the colon by chemopreventative agents such as ethoxyquin, butylated hydroxyanisole, and sulforaphane.…”
Section: Discussionmentioning
confidence: 99%
“…Recently GST has been identified as an endogenous protein binding partner and regulator of c-Jun NH 2 -terminal kinase (JNK) and peroxiredoxin VI (1-cysPrx) (4 -6). Moreover, oxidative stress causes increased GST expression, the regulation of which has been identified as a downstream event linked to wild-type p53 function (7). Cellular response to oxidative or nitrosative stress includes S-glutathionylation, a post-translational modification characterized by conjugation of glutathione to low pK cysteine sulfhydryl or sulfenic acid moieties in target proteins.…”
mentioning
confidence: 99%